The geography of rail freight transport and the flows of mineral-based raw materials in Brazil - Pereira, Luiz Andrei Gonçalves Pereira (Geografares, 2026)
In spatial interactions, railways play a strategic role in the (re)organization of freight flows, which require connections and intersections of infrastructure, as well as the provision of transport services in the movement of mineral products across the Brazilian territory. The purpose of this article was to analyze the socio-spatial dynamics of the rail transport system in the circulation of mineral-based raw material shipments in Brazil, considering the flows on the routes between the origin and destination rail stations of the transported products, in the period from 2006 to 2025. The methodological procedures were structured in the literature review, collection, tabulation, and analysis of data provided by the National Land Transport Agency of Brazil (ANTT). Mineral product shipments were concentrated in the states of Minas Gerais and Pará, being predominantly transported via the Carajás Railway, the Vitória-Minas Railway, and MRS Logística, connecting the port complexes of São Luís, Vitória, and Itaguaí.